PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN INFORMASI STRATEGIS PADA WEBSITE PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010) - Firda Amalia; Herry Laksito (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to determine the influence of corporate governance mechanismtowards the volume of strategic information disclosed on corporate website. The variables breakeddown into meeting frequency of The Board of Commisioner, the size of Board of Commisioner,Independent Board of Commisioner’s composition and Blockholder’s ownership. The AgencyTheory, Signaling Theory, and Proprietary Cost Theory are used to explain the relation amongthose variables. This study is a replica of the prior research that has been done by Sanchez et al.,(2011) with the constriction of research’s samples. This study is a cross-sectional study, wheresecondary data of 36 websites and annual reports of manufacturing companies listed in BEI for2010 are used. The statistic method used to examine the hypothesis is Linear Regression with SPSS17.0. The results indicate that the meeting frequency of Board of Commisioner has a positive andsignificant influence to the volume of strategic information disclosed on corporate website. Whilethe size of Board of Commisioner, Independent Board of Commisioner’s composition andBlockholder’s ownership proven nothing influence to the volume of strategic information disclosedon corporate website.